A172: Metaphyseal Chondrodysplasia, Ectodermal Dysplasia, Short Stature, Hypergammaglobulinemia, and Spontaneous Inflammation Without Infections in an Extended Family Due to Mutation in NFKB1A. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Oberle, Edward J.; Verbsky, James W.; Routes, John; Hintermeyer, Mary; Worthey, Elizabeth; Dasu, Trivikram; Bengtson, Christine; Buzzell, Alyssa
Abstract : Background/Purpose: Autoinflammatory disorders are characterized by chronic inflammation and a variety of systemic complaints. Defects in the NF‐kB essential modifier pathway, or NEMO, are associated with an immune deficiency characterized by ectodermal dysplasia. We investigated an extended family with features of both chronic inflammation and NEMO following an autosomal dominant inheritance. Methods: Eight individuals from one family were evaluated. The proband, a male patient age 12 with known hypohydrosis, presented to our rheumatology clinic for chronic articular pain with bony hypertrophy of wrists, knees, and ankles. Plain radiographs and standard labs were obtained including ESR, CRP, CBC, and immunoglobulins for all affected individuals. Films were reviewed by two musculoskeletal radiologists. The proband underwent a proximal tibial bone biopsy, as well as genetic testing for known autoinflammatory disorders and mutations in NF‐kB pathway. The Tolllike Receptor (TLR) assay was used to evaluate NF‐kB function. Results: The proband, his father age 30, two brothers age 7 and 9, and his 2‐year‐old sister were all found to have ectodermal dysplasia, short stature and failure to thrive, chronic inflammation, elevated WBC, and hypergammaglobulinemia (Figure1 ). Radiographs of proband displayed sclerotic lesions of the metaphyses of distal radius/ulna, distal femora, and proximal and distal tibia/fibula (Figure2 ). The patient's father was evaluated as a child for bone issues, and radiographs demonstrate widened metaphyses of distal ulna and tibia. Bone biopsy of the proband was consistent with metaphyseal chondrodysplasia. Genetic testing for known autoinflammatory disorders was negative while testing of the NFKB1A gene demonstrated a heterozygous mutation (W11X). TLR responses were normal in two affected individuals indicating intact NF‐kB signaling. No infections were noted in the family. Conclusion: This series demonstrates the clinical variability that can occur due to mutations in NFKB1A. Infections were not prevalent in this family, but spontaneous inflammation was common. In addition, this is the first report of metaphyseal chondrodysplasia as a complication of NEMO or related disorders.